Community Strengthening in Health Behavior Modification for Prevention and Controlling Diabetes Mellitus and Hypertension using Local Wisdom - พันธุลาวัณย์, โสภาพร (วารสารวิจัยการพยาบาลและสุขภาพ, 2018)
This study aimed to describe health behaviors and to identify local wisdoms in prevention and controlling diabetes mellitus (DM) and hypertension, and to apply local wisdoms for health behavior modification in order to control DM and hypertension. Participants composed of community leader, folk philosophers, community volunteer of a healthy group, a risk group, and a group of people with DM and hypertension. Data collection included: health surveying to identify health behaviors, exploring local wisdoms and identifying a methodology for health modifications using local wisdoms Results revealed that the participants used the seasoning added to food primarily for the savor. DM and hypertensive patients reported that alcohol was used to eliminate their stress (91.11%). There were natural herbs in the community for preventing and controlling diabetes mellitus and hypertension. Honey can reduce alcohol drinking. Murraya siamensis Craib (Prong Fah) can reduce smoking. After using local wisdoms for health modifications, the participants with hypertension had lower blood pressure in 1 month (137.5/82 mmHg) 2 months (136/77.5 mmHg) and 3 months (134.5/77.3mmHg) compared to before intervention 137.5/82mmHg). DM patients had lower blood glucose level in 1 month (147mg/dl) 2 month (132.5mg/dl) and 3 months (111 mg/dl) compared to before intervention (147 mg/dl). For alcohol and cigarette cessation, using local wisdoms reduced alcohol and cigarette consumption behavior. The ongoing of activities and strengthening rural communities to apply local wisdoms for health behavior modification in order to control DM and hypertension included: government to encourage ongoing activities, community leader to encourage behaviors in prevention and controlling diabetes mellitus and hypertension, knowledge sharing to new generation and recognize individuals with practical and a good role model.